Clinical, laboratory and genetic factors associated with smoking in a Brazilian Sickle Cell Disease (SCD) cohort - Theomario Cruz; Beatriz Araujo Oliveira; Mina Cintho Ozahata; Isabel Gomes; André Belisário; Anna Bárbara Carneiro-Proietti; Paula Loureiro; Sheila de Oliveira Garcia Mateos; Cecília Salete Alencar; Rodrigo Oliveira; Frederico L. A. Fernandes; Shannon Kelly; et al. (PLoS ONE, 2025)
Background Smoking is associated with increased morbidity among individuals with sickle cell disease (SCD). While genetic factors influencing smoking behavior have been identified in other populations, they have not been studied in individuals with SCD. This study aimed to assess the impact of smoking on clinical and laboratory parameters in a large SCD cohort and to identify genetic variants potentially associated with smoking behavior in this population. Methods The Recipient Epidemiology and Donor Evaluation Study-III (REDS-III) Brazil SCD cohort was established across six Brazilian cities to investigate clinical outcomes in individuals with SCD. Adult participants were interviewed and asked whether they had ever smoked more than 100 cigarettes in their lifetime. Those who responded “yes” were classified as ever smokers, while those who responded “no” were classified as never smokers. Clinical and laboratory data were compared between the two groups. All participants were genotyped using a customized array, and a genome-wide association study (GWAS) was conducted to identify single nucleotide variants (SNVs) associated with smoking status. Results Of the 1,231 adults with available smoking data, 332 (27%) were classified as ‘ever smokers’ and 899 (73%) as ‘never smokers’. ‘Ever smoker’ status was associated with male sex, age ≥ 40 years, lower educational attainment, and hemoglobin levels above the 75th percentile. In the GWAS, no SNVs reached genome-wide significance (p < 5 × 10 ⁻ ⁸). However, several SNVs demonstrated nominal significance (p < 1 × 10 ⁻ ⁷), including rs11087854 and a variant at position 1059991 on chromosome 20 within the gene AL110114.1, as well as rs701023 in the NCOR2 gene, suggesting a potential association with smoking behavior. Conclusion Biological sex, age, and educational level are associated with smoking status among adults with SCD, and tobacco use appears to correlate with elevated hemoglobin levels in this population. Although no genome-wide significant associations were identified, our findings highlight potential genetic loci—particularly within AL110114.1 and NCOR2—that warrant further investigation in relation to smoking behavior in individuals with SCD.